Integrative transcriptome analysis of triple negative breast cancer profiles for identification of druggable targets - Arumugam, Poornima; Ramesh, Vignesh; Sampathkumar, Banupriya; Perumalsamy, Haribalan; Balusamy, Sri Renukadevi; Suganya, Kanagaraj; Balraj, Sudha; Nachimuthu, S. Kumar; Sundaravadivelu, Sumathi (Journal of biomolecular structure & dynamics, 2023)
As triple negative breast cancer (TNBC) lacks a specific target, exploration of abnormally expressed genes during the progression of TNBC is important for a better understanding of tumorigenesis and to find a specific target. We intended to figure out genes associated with TNBC, which can provide unique insights into gene dysregulation in TNBC while also pointing to new possible therapeutic targets for TNBC. A meta-analysis of multiple TNBC mRNA profiles was performed to identify consistently differentially expressed genes (CDGs). The pathways involved in modulating these genes were analyzed by MsigDB, and the interaction map was constructed. These CDGs were evaluated for their expression in cell lines, and drugs that could modulate the expression of CDGs were obtained using the connectivity map. CDGs were docked with doxorubicin and anethole, which is a phytocompound. The expression of selected CDGs was analyzed in MDA-MB-231 cells after treatment with doxorubicin and anethole. We found 45 CDGs, out of which 36 were upregulated and 9 were downregulated. MDA-MB-231 cell line was found to have high expression of CDGs, and drug that could modulate the expression of CDGs was doxorubicin. Docking results revealed that anethole and doxorubicin had good interaction with the CDGs especially with the genes AURKA, CDC6, DEPDC1, KIF23, KPNA2, MELK, CTNNB1, FLI1 and E2F1. Gene expression studies of the selected CDGs showed that the synergistic effect of anethole and doxorubicin effectively downregulated the expression. The CDGs identified from multiple cohorts have clinical significance and may be effectively exploited in the targeted therapy for TNBC. Communicated by Ramaswamy H. Sarma.
CRIS-Team Scopus Importer:2023-02-03
Keywords: anethole; docking; doxorubicin; transcriptomic profiles; Triple negative breast cancer